2022
DOI: 10.3389/fonc.2022.906501
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Shear Wave Elastography, Microvascular Doppler Ultrasound Technique, and BI-RADS for the Differentiation of Benign and Malignant Breast Masses

Abstract: ObjectiveTo evaluate the value of the combined use of Breast Imaging Reporting and Data System (BI-RADS), qualitative shear wave elastography (SWE), and AngioPLUS microvascular Doppler ultrasound technique (AP) for distinguishing benign and malignant breast masses.Materials and MethodsA total of 210 pathologically confirmed breast lesions in 210 patients were reviewed using BI-RADS, qualitative SWE, and AP. The sensitivity, specificity, negative predictive value (NPV), positive predictive value (PPV), accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
4
16
1
Order By: Relevance
“…In addition, Wang and coworkers suggested the highest AUC value of 0.861 combined BI-RADS with SWE and AP. 13 The above results were all consistent with our findings of AP + SWE in serial.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, Wang and coworkers suggested the highest AUC value of 0.861 combined BI-RADS with SWE and AP. 13 The above results were all consistent with our findings of AP + SWE in serial.…”
Section: Discussionsupporting
confidence: 91%
“…However, the previous study reported that the sensitivity, specificity, PPV, and NPV of performing SWE alone were 83.6%, 79.0%, 65.1%, and 91.1%, respectively. 13 The discrepancies may firstly be due to the different study populations, since the previous work collected mainly ML lesions, while our study emphasized NML lesions. Secondly, the stiffness of ML is considered to be more pronounced than NML due to its relatively clear boundaries and confined range, thus may be the reason to affect the diagnostic performance of SWE.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations